2017
DOI: 10.1186/s12883-016-0781-2
|View full text |Cite
|
Sign up to set email alerts
|

A limb-girdle myopathy phenotype of RUNX2 mutation in a patient with cleidocranial dysplasia: a case study and literature review

Abstract: BackgroundCleidocranial dysplasia (CCD) is a rare hereditary disorder that arises from heterozygous loss of function mutations in the runt-related transcription factor 2 (RUNX2) gene. As RUNX2 is mainly expressed in osteoblasts, CCD typically affects the skeletal and dental systems. Few studies have investigated RUNX2 mutation effects on non-skeletal systems. Here, we describe limb-girdle myopathy, an uncommon phenotype of CCD, in a patient with a heterozygous missense mutation (p.R225Q) in the RUNX2 gene.Case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The interpretation may be supported by the findings of several soft tissue studies, which revealed a masseter muscle volume reduction in CCD patients [ 33 , 34 ]. Some clinical case reports revealed their CCD patients present with muscle weakness [ 35 , 36 ]. Moreover, loss of Runx2 results in reduced expression of pro-myogenic secreted factors, such as Aldh1a2, Igf1, Cxcl12, and Cthrc1, which may affect muscle proliferation and differentiation in mouse model [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The interpretation may be supported by the findings of several soft tissue studies, which revealed a masseter muscle volume reduction in CCD patients [ 33 , 34 ]. Some clinical case reports revealed their CCD patients present with muscle weakness [ 35 , 36 ]. Moreover, loss of Runx2 results in reduced expression of pro-myogenic secreted factors, such as Aldh1a2, Igf1, Cxcl12, and Cthrc1, which may affect muscle proliferation and differentiation in mouse model [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The phenotypic spectrum of CCD may be varied. CCD exhibits autosomal dominant heredity with an approximate prevalence of 1:1,000,000 [ 3 ].…”
Section: Introductionmentioning
confidence: 99%